À la croisée de l’école, de l’art et de l’industrie du livre : concevoir et choisir un manuel de lecture à partir de la littérature de jeunesse en C.P. - Samuel Pinto (Cahiers de la Recherche sur l'Education et les Savoirs)
This work aims to understand how, between school and publishing market, reading learning with children’s literature in C.P has emerged. For this, we observed the editorial constraints on text books based on children’s literature and the pedagogical and financial constraints on teachers when they choose their school book. Then, we analyzed the sociocultural presuppositions related to learning to read. It appears that it has developed on cultural assumptions and development of the “reading pleasure”.